Enhancing UI/UX Design Competency Using Figma at SMK NU Donomulyo - Adriani Kala'lembang; Suastika Yulia Riska; Azwar Riza Habibi; Widya Adhariyanty Rahayu; Yudistira Arya Sapoetra (Institut Teknologi dan Bisnis Asia Malang, 2026)
Purpose: This study addresses the competency gap between vocational graduates and industry demands for UI/UX design skills through a Figma-based training program at SMK NU Donomulyo. Method: A hands-on, project-based workshop was delivered to 30 students. Effectiveness was measured via pre-test/post-test assessments, final project rubrics, and participant satisfaction surveys. Practical Applications: The program provides students with industry-standard prototyping capabilities and ready-to-use digital portfolios, directly improving their employability in the growing digital design sector. Conclusion: Findings revealed a 40.6% knowledge improvement, 100% project completion, and high satisfaction (4.5/5.0). The initiative successfully bridges educational and industrial requirements, confirming hands-on training as a vital strategy for vocational digital readiness.